Functional Characterization of the MYO6 Variant p.E60Q in Non-Syndromic Hearing Loss Patients - Moza Alkowari (18288922) (2022)
Hereditary hearing loss (HHL) is a common genetic disorder accounting for at least 60% of pre-lingual deafness in children, of which 70% is inherited in an autosomal recessive pattern. The long tradition of consanguinity among the Qatari population has increased the prevalence of HHL, which negatively impacts the quality of life. Here, we functionally validated the pathogenicity of the c.178G>C, p.E60Q mutation in the MYO6 gene, which was detected previously in a Qatari HHL family, using cellular and animal models. In vitro analysis was conducted in HeLa cells transiently transfected with plasmids carrying MYO6WT or MYO6p.E60Q, and a zebrafish model was generated to characterize the in vivo phenotype. Cells transfected with MYO6WT showed higher expression of MYO6 in the plasma membrane and increased ATPase activity. Modeling the human MYO6 variants in zebrafish resulted in severe otic defects. At 72 h post-injection, MYO6p.E60Q embryos demonstrated alterations in the sizes of the saccule and utricle. Additionally, zebrafish with MYO6p.E60Q displayed super-coiled and bent hair bundles in otic hair cells when compared to control and MYO6WT embryos. In conclusion, our cellular and animal models add support to the in silico prediction that the p.E60Q missense variant is pathogenic and damaging to the protein. Since the c.178G>C MYO6 variant has a 0.5% allele frequency in the Qatari population, about 400 times higher than in other populations, it could contribute to explaining the high prevalence of hearing impairment in Qatar. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms23063369